Intelligent Systems for Social Good Theory and Practice - Mukherjee, Shyamapada; Muppalaneni, Naresh Babu.; Bhattacharya, Sukriti; Pradhan, Ashok Kumar (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This book highlights the connections between two technologies: artificial intelligence (AI) and Internet of things (IoT). It presents the application of these two technologies to solve various societal problems related to healthcare, agriculture, green environment, renewable energies, smart cities, etc. Each chapter in this book presents novel solutions to these problems along with the challenges in the application of AI and IoT to solve them. It discusses the adverse attacks on machine Learning models and how to protect sensitive data over the IoT networks. It also includes the security issues in IoT and their possible solutions.
Chapter 1 - ML in WSN Using IoT for Smart Cities: A Survey (Piyush Raja) -- Chapter 2 - Prospects of 'SMART Farming' in Cold Arid Region of Ladakh, India (S. Angchuk, Aleem Ali) -- Chapter 3 - Integration of Artificial Intelligence and IoT on Agricultural Applications (Yaswanth Bhanu Murthy M, Sk.Enaul Haq, Koteswararao Anne, Sunil Babu M) -- Chapter 4 - Internet of Things based Smart Transportation System for Smart Cities (E. Fantin Irudaya Raj, M. Appadurai) -- Chapter 5 - Faceify : Intelligent System for Text to Image Translation (Shyamapada Mukherjee, Satya Sanjay Nath, Gobind Kumar Singh, Sumanta Banerjee) -- Chapter 6 - LiFi Technology: A Breakthrough for Massive Data Rates in Indoor Applications (Rahul Sharma, Devendra Singh Gurjar, Elvis Rahman, Aditya Raghav, Pranjal Shukla, and Vivek Mishra) -- Chapter 7 - Fuel Larceny and Leakage Indication System using IoT (Prasanna Palsodkar, Prachi Palsodkar, Aniket Gokhale, Prabhakar Dorge, Ajay Gurjar) -- Chapter 8 - IoT Applications for Health Care (Shiva Agarwal) -- Chapter 9 - Smart Healthcare Remote Monitoring System using Internet of Things (Shyamapada Mukherjee, Rahul Kumar, Sumanta Banerjee) -- Chapter 10 - Data Privacy in IoT Network using Blockchain Technology (Tamar Das, Shyamapada Mukherjee) -- Chapter 11 - Interval-valued fuzzy parameterized multi fuzzy N-soft set in decision-making (Ajoy Kanti Das and Carlos Granados) -- Chapter 12 - An innovative approach to fuzzy soft set based investment framework using machine learning algorithm (Ajoy Kanti Das and Carlos Granados) -- Chapter 13 - A Design and implementation of Ring Oscillator Physically Unclonable Function using the Xilinx FPGA (Swati Kulkarni, Vani R.M., P.V. Hunagund) -- Chapter 14 - IOT based Automated Fish Tank (Yashika Gaidhani, Manisha Waje, Monica Kalbande, Tejswini Panse) -- Chapter 15 - Cloud Based Examination Hall Authentication System using fingerprint module (Monica Kalbande, Yashika Gaidhani, Tejswini Panse, Mahadev Mahajan) -- Chapter 16 - Pandemic Surveillance through Perspective Transformation Using YOLO and Mobile Net (Prachi Palsodkar, Prasanna Palsodkar, Yogita Dubey, Roshan Umate).
Keywords: Internet of things; Artificial intelligence; Machine learning; Computational intelligence; Internet of Things; Artificial Intelligence; Machine Learning; Computational Intelligence